Squaramate-Modified Nucleotides and DNA for Specific Cross-Linking with Lysine-Containing Peptides and Proteins - Ivancová, Ivana; Pohl, Radek; Hubálek, Martin; Hocek, Michal (Angewandte Chemie (International ed. in English), 2019)
Squaramate-linked 2'-deoxycytidine 5'-O-triphosphate was synthesized and found to be good substrate for KOD XL DNA polymerase in primer extension or PCR synthesis of modified DNA. The resulting squaramate-linked DNA reacts with primary amines to form a stable diamide linkage. This reaction was used for bioconjugations of DNA with Cy5 and Lys-containing peptides. Squaramate-linked DNA formed covalent cross-links with histone proteins. This reactive nucleotide has potential for other bioconjugations of nucleic acids with amines, peptides or proteins without need of any external reagent.
Keywords: lysin; DNA polymerase; Proteins; lidé; DNA; cross-linking reactions; Peptides; proteiny; nukleotidy; Humans; proteins; bioconjugation; Nucleotides; peptidy; Lysine